Undead and undermined [large type] - Davidson, MaryJanice (Thorndike Press large print core series., 2011)
So this is what being dead feels like. Vampire queen Betsy Taylor has awoken in a Chicago morgue, naked as a corpse. Her last memory is reconciling with her husband, Eric Sinclair, after a time-traveling field trip, including an indirect route to hell (literally), with her sister, Laura. Now she's Jane Doe #291, wrapped in plastic with a toe tag. Betsy can't help but wonder, what in hell happened? Grabbing clean scrubs, Betsy hits the pavement and heads back to her St. Paul mansion to find everyone frantically searching for her.